2013
DOI: 10.1590/s1679-62252013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetics in Astyanax (Characiformes: Characidae) with focus on the cytotaxonomy of the group

Abstract: Astyanax is a diverse group of Neotropical fishes, whose different forms occupy different environments. This great diversity is also reflected on cytogenetic aspects and molecular markers, which have repeatedly been demonstrated by cytogenetic studies. In order to characterize the karyotype of species of this genus, six species were studied: Astyanax altiparanae, A.argyrimarginatus, A. elachylepis, A. xavante, and two new species provisionally called Astyanax sp. and A. aff. bimaculatus. A detailed cytogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The genus Astyanax displays variability among species with respect to chromosome structure, number, and morphology (see, for example, Morelli et al 1983;Almeida-Toledo 2001, 2005;Tenório et al 2013). However, the current study showed that the H3 histone gene locations were conserved among species, particularly with Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Astyanax displays variability among species with respect to chromosome structure, number, and morphology (see, for example, Morelli et al 1983;Almeida-Toledo 2001, 2005;Tenório et al 2013). However, the current study showed that the H3 histone gene locations were conserved among species, particularly with Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors described different numbers of chromosomes bearing NORs in the genus Astyanax. 6,10,[22][23][24][25] According to Tenório et al, 11 six Astyanax species had different Ag-NOR numbers. One pair was observed in Astyanax argyrimarginatus, Astyanax aff.…”
Section: Discussionmentioning
confidence: 99%
“…Among Astyanax species, and among populations of the same species, these markers have both conserved and divergent features. [9][10][11][12] In this study, we used various cytogenetic markers to obtain new chromosomal data for A. altiparanae and Astyanax eigenmanniorum, and to describe, for the first time, the karyotype of Astyanax abramis. Our findings contribute to the understanding of chromosomal evolution in the genus Astyanax.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several classes of repetitive DNAs have been physically mapped in different Astyanax species, providing important clues about karyotype diversification at intra and inter-specific levels (Kavalco and Moreira-Filho 2003;Kavalco et al 2011Kavalco et al , 2012Hashimoto et al 2011;Pansonato-Alves et al 2013;Silva et al 2013;Tenório et al 2013). For instance, the chromosomal location of 5S rDNA and H1 histone sites is remarkably conserved in different species (Mantovani et al 2005;Hashimoto et al 2011).…”
Section: Physical Mapping Of Known Repetitive Dna Familiesmentioning
confidence: 99%